"There is no one who helps you with it": experiences of people with long COVID regarding medical care, therapeutic measures, and barriers in the German healthcare system: results of a qualitative study with four focus groups - Tim Schmachtenberg; Gloria Königs; Anita Dragaqina; Sascha Roder; Frank Müller; Christina Müllenmeister; Dominik Schröder; Alexandra Dopfer-Jablonka; Katharina Vieth; Iman El-Sayed (BMC, 2023)
Abstract Background Many people experience long-term symptoms such as fatigue, cognitive problems, or shortness of breath after an acute infection with COVID-19. This emerging syndrome, known as long COVID, is new and complex in many aspects. This study aims to collect the experiences of people with long COVID with ambulatory healthcare structures. Methods Four focus groups were conducted with a total of 23 adults with long COVID in June and July 2022. These discussions were audio-recorded, subsequently transcribed, and analyzed using the qualitative content analysis of Mayring and Kuckartz. Results Fourteen out of 19 participants who had a primary care encounter regarding their long COVID symptoms did not perceive it as helpful. Many respondents reported that their general practitioners did not take their long COVID symptoms seriously and did not refer them to specialists or made therapeutic recommendations. However, some participants reported that they were prescribed non-pharmaceutical therapies (e.g., group meetings supported by psychotherapists, occupational therapy, etc.) that improved their condition. 14 of 23 respondents perceived care barriers such as providers' lack of awareness of long COVID, poor access to specialists, a lack of specialized care (e.g., long COVID clinics), or high bureaucratic hurdles for specific healthcare services. To improve medical care, participants suggested campaigns to raise awareness of long COVID among healthcare providers and the general population, increase research and government investments regarding the development of treatment structures for long COVID, expanding existing therapeutic services, and establishing one-stop shops for integrated specialist healthcare for people with long COVID. Conclusions Several implications for healthcare professionals and policymakers can be derived from this study: (1) general practitioners should take the symptoms of long COVID seriously, assume a care coordinating role, make referrals, and establish contact with long COVID clinics; (2) care planners should focus on developing interprofessional evidence-based care and treatment approaches for long COVID; (3) existing care structures such as long COVID outpatient clinics should be expanded. The overarching goal must be to develop consistent guidelines for long COVID diagnosis, care, and treatment. Trial registration The study is registered in the German register for clinical trials (DRKS00026007, first registration on 09/09/2021).